Neurodevelopmental Outcomes of Children Following In Utero Exposure to Zika in Nicaragua. (30th January 2021) - Stringer, Elizabeth M; Martinez, Evelin; Blette, Bryan; Toval Ruiz, Christian Eduardo; Boivin, Michael; Zepeda, Omar; Stringer, Jeffrey S A; Morales, Marlen; Ortiz-Pujols, Shiara; Familiar, Itziar; Collins, Matthew; Chavarria, Meylin; et al.
Abstract: Background: Neurodevelopmental outcomes of asymptomatic children exposed to Zika virus (ZIKV) in utero are not well characterized. Methods: We prospectively followed 129 newborns without evidence of congenital Zika syndrome (CZS) up to 24 months of age. Participants were classified as ZIKV exposed or ZIKV unexposed. The Mullen Scales of Early Learning (MSEL) was administered in the participants' homes at 6, 12, 15, 18, 21, and 24 months of age by trained psychologists. Sociodemographic data, medical history, and infant anthropometry at birth were collected at each home visit. Our primary outcome was the Mullen Early Learning Composite Score (ECL) at 24 months of age between our 2 exposure groups. Secondary outcomes were differences in MSEL subscales over time and at 24 months. Results: Of 129 infants in whom exposure status could be ascertained, 32 (24.8%) met criteria for in utero ZIKV exposure and 97 (75.2%) did not. There were no differences in maternal age, maternal educational attainment, birthweight, or gestational age at birth between the 2 exposure groups. The adjusted means and standard errors (SEs) for the ELC score between the ZIKV-exposed children compared to ZIKV-unexposed children were 91.4 (SE, 3.1) vs 96.8 (SE, 2.4) at 12 months and 93.3 (SE, 2.9) vs 95.9 (SE, 2.3) at 24 months. In a longitudinal mixed model, infants born to mothers with an incident ZIKV infection ( P = .01) and low-birthweight infants (<2500 g) ( P = .006) had lower composite ECL scores. Conclusions: In this prospective cohort of children without CZS, children with in utero ZIKV exposure had lower neurocognitive scores at 24 months. Abstract : Children with in utero Zika virus exposure and without congenital Zika syndrome in Nicaragua had lower neurocognitive scores at 24 months. Our study includes multiple evaluations over time and a contemporary nonexposed comparator group of children, which is currently lacking in the literature.